A Conversation with Zia Sardar. Issue 2 (19th May 2022) - Mayo, Liam
Abstract: These are excerpts of a conversation with Ziauddin Sardar in early 2020. Zia gives his definition of postnormal times: how it describes the rapid nature of change, and how it describes the changing nature of change itself. He confronts the inevitability of postnormality given the erosion of trust in politics, and in the spread of fake news and disinformation. It is a characterization of the "hanging between, " the period in between the end of one paradigm and the emergence of another. Given that, it is our obligation to consider the unthought, to drop our assumptions and precepts from the past to navigate to desirable futures. Postnormal times theory is also a theory of change that incorporates the pace of change and resulting complexity, contradictions, and chaos. Unsurprisingly, Zia criticizes postmodernism and distances postnormal analysis from it in no uncertain terms. It is uncertain how long the transition may be to a new paradigm, a new normal, perhaps centuries, but the fact remains, we cannot control postnormal times, simply navigate them.